THU0446 Trabecular bone texture parameters are correlated with magnetic resonance imaging (MRI) bone edema at hand and wrist in active rheumatoid arthritis (RA). (23rd January 2014) - Pham, T.; Trijau, S.; Chapurlat, R.; Loeuille, D.; Schaeverbeke, T.; Roux, C.; Benhamou, C.L.; Vittecoq, O.; Sibilia, J.; Mistretta, F.; Hacquard-Bouder, C.
Abstract : Background: In RA, bone marrow edema (BME) is predictive of erosive progression. Bone erosions are assumed to appear through activation of local bone resorption mechanisms, reflected by periarticular osteopenia. Measurement of periarticular bone mineral density by DXA requires specific hand software limiting its application in large population, and does not assess bone texture. A new high resolution direct digital X-ray device has been recently developed to provide bone texture analysis reflecting changes in trabecular bone architecture, with a very low radiation exposure. Objectives: To assess the correlation between MRI bone edema and trabecular bone texture parameters in active RA. Methods: Study design: cross-sectional multicenter study. Comparative MRI and high resolution X-rays of the dominant hand and wrist were obtained from 55 patients with active RA according to ACR/EULAR criteria (DAS 28 ≥3.2). Clinical examination and radiographs of the hands and feet were also performed. High resolution direct digital X-ray (BMA™, D3A Medical Systems): The fractal trabecular bone texture parameter (Hmean) was evaluated on the 2nd and 3rd metacarpal head, capitatum and lunatum. MRI: BME was scored according to the RA MRI score (RAMRIS) by two independent and experienced radiologists (central reading). BME was also specifically assessed on the 4 bones where Hmean was evaluated (BME4 score). Radiographs: plain radiographs were scored using the modified Sharp-van der Heijde method. Analysis: Inter-reader reliability: ICC. Correlation between BME and Hmean: Spearman test. Results: Data from 53 patients were analyzable. The main patients characteristics were (mean ± SD): age 57±14 years, 75% women, disease duration 8.6±9.2 years, DAS28 5.4±1.3, anti-CCP 76%, Sharp-DvdH 23.8±31.3, currently treated with DMARDs 74%, biologics 47%, corticosteroids 60% (mean daily dosage 9.1±6.6 mg). The mean ± SD [median] RAMRIS BME, BME4 and Hmean scores were 12.7±14.6 [5.0], 2.7±2.8 [1.0] and 0.60±0.06 [0.61], respectively. RAMRIS BME inter-reader reliability: ICC=0.96. Correlations between Hmean and both RAMRIS BME and BME4 scores were r=-0.31 (p=0.022) and r=-0.32 (p=0.018), respectively. When evaluated only on the 2nd and 3rd metacarpal head, Hmean was significantly correlated with the total BME score r=-0.28 (p=0.038) whereas it was not when evaluated on lunatum and capitatum (r=-0.22 – p=0.120). Conclusions: This study demonstrated trabecular bone texture parameter is correlated to MRI bone edema scores. It would be interesting to assess if bone texture impairment, measured with a high resolution digital X-ray device, could predict RA radiographic progression in a wider range prospective study. Disclosure of Interest: T. Pham Consultant for: Abbott, S. Trijau: None Declared, R. Chapurlat Consultant for: Abbott, D. Loeuille Consultant for: Abbott, T. Schaeverbeke Consultant for: Abbott, C. Roux Consultant for: Abbott, C. L. Benhamou Consultant for: Abbott, O. Vittecoq Consultant for: Abbott, J. Sibilia Consultant for: Abbott, F. Mistretta Consultant for: Abbott, C. Hacquard-Bouder Employee of: Abbott